An unusual complication of central venous catheterization - Vignesh Kumar Chandiraseharan; A R Malathy (Wolters Kluwer Medknow Publications, 2015)
An 87-year-old female, a known case of diabetes mellitus was admitted with acute febrile illness with altered sensorium and uncontrolled hyperglycemia. She was evaluated and diagnosed to have urosepsis, septic shock and lactic acidosis. In view of the difficulty in securing a peripheral intravenous line, a central venous catheterization was performed. Though nonpulsatile venous blood was aspirated from the needle initially, blood stained serous fluid was aspirated after insertion of the catheter. The fluid was analyzed and found to have high triglyceride concentration suggesting that it was lymph. A chest X-ray was taken which too confirmed malposition of the catheter. This case represents a rare complication of right thoracic duct cannulation during central venous catheterization of the right internal jugular vein (IJV), when anecdotal reports advice preferring right IJV to left in view of possible thoracic duct cannulation.